Transtympanic delivery of the pneumococcal endolysin MSlys via PEGylated liposomes - Silva, Maria Daniela Ferreira (2022)
[Excerpt] Introduction: Streptococcus pneumoniae is the most common pathogen that causes acute otitis media [1]. For decades, systemic antibiotic therapy has been the gold standard treatment for these infections. However, the increasing antibiotic resistance has prompted research for novel topical antibiotic alternatives. Endolysins, peptidoglycan hydrolases encoded by bacteriophages, have attracted a lot of attention, even for controlling S. pneumoniae [2]. Nevertheless, the efficacy of topically applied endolysins is impaired by the trilaminar tympanic membrane (TM), that acts as protective barrier preventing the permeation of compounds from the ear canal into the middle ear. Liposomal formulations, including PEGdecorated liposomes, have been shown to improve drug permeation through the TM. We have previously characterized a novel pneumococcal endolysin (MSlys) [2] and its encapsulation in liposomes, which were physicochemically characterized and assessed with regards to the in vitro release, cytotoxicity and antipneumococcal activity [4]. However, little remains known about its permeation ability and subsequent activity through an intact TM. In this study, we evaluated the permeation ability of MSlys-loaded PEGylated liposomes across different ex vivo models and compared it to the permeation of the free MSlys.[...]